Hubungan Jenis dan Frekuensi Makan dengan Suspect Dispepsia Mahasiswa S1 Keperawatan UNJA - Ulfa, Nurmaliza; Nurlinawati, Nurlinawati; Yuliana, Yuliana (Jurnal Ilmiah Ners Indonesia, 2021)
Dyspepsia is the biggest disease in Jambi Province which ranks 9th. The influence factors occurrence of dyspepsia are the type and frequency of eating. Irregular eating habits and consuming spicy, acidic, fatty foods, coffee and soft drinks can cause dyspepsia. The purpose of the study was to know the relationship between type and eating frequency with number of suspect dyspepsia at Sarjana Degree nursing Students of Jambi University. This research is a quantitative correlational research with a cross sectional approach. Sampling using a total sampling technique of 106 samples. The instrument used was a questionnaire on the type and frequency of eating and a Suspect Dyspepsia questionnaire via google form. Data analysis using Chi Square. The results of this study showed that 41 respondents (38.7%) was suspected dyspepsia, 65 respondents (61.3%) was negative dyspepsia. the type of eating less well 64 respondents (60.4%), good was 42 respondents (39.6%). Meanwhile, the frequency of eating irregularly was 59 respondents (55.7%), while eating regularly was 47 respondents (44.3%). The results of the study on the type and frequency of eating obtained p-values of 0,000 and 0,023 <0,05, so there is a significant relationship between the type and frequency of eating with number of suspect dyspepsia at Sarjana Degree nursing Students of Jambi University.